Surfactant Induced Eriochrome Cyanine R-Metal Ion Interactions: Complexation and Analytical Studies - Joshi, S.P.; Mahakalkar, A.S.; Munshi, K.K. (Asian Journal of Chemistry, 2010)
The chelation reactions of some rare earths in the presence of cetyltrimethyl ammonium bromide (CTAB) and tritron X-100(TX) have been studied in detail. The complexes show a large bathochromic shift. The composition of the chelates of uranium with erichrome cyanine-R (ECR) was found to be 1 : 1 in the absence of surfactant and 1 : 2 in the presence of CTAB and TX. However, the composition of Th4+, Y3+ and Eu3+ with ECR was found to be 1 : 2, both in the absence and presence of CTAB of TX. The stability constants were evaluated. Various analytical parameters were evaluated to prove the utility of ECR in the spectrophotometric microdetermination of metal ions under study. The effect of foreign ions on the systems was studied in the presence of large number of cations and anions.